Experimental Analysis of Cable Distance Effect on Signal Attenuation in Single and Multimode Fiber Optics - Uzairue Stanley; Victor Matthews Olu; Charles Ochonogor; Amaize Peter; Anyasi Francis (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Losses during transmission and high demand of high data rate by the end users have become the biggest challenges facing the telecommunication industries worldwide with Nigeria inclusive. Fiber optic cable as a channel of communication has been adapted worldwide in solving these problems but there is a little limitation in the place of multimode fiber in long distance communication. This paper focuses on the effect of changes in distance on transmitted bandwidth on single mode and multimode fiber. Two cases were considered during this research; (a) with optical amplifier placed in between multimode fiber and (b) without optical amplifier in between multimode fiber. Readings were taken at various distances when specific bandwidth ranging from 50Mbps to 500Mbps was transmitted from the base station to the various distances and it was observed that there was no significant changes in bandwidth received at specified distances (100, 200, 300, 400, 500 etc) m when using single mode fiber, there was a drastic reduction in bandwidth when it get to a distance of 300m when using multimode. When optical amplifier was placed in between the multimode fiber at some selected distances after 400m from the transmitting BTS, it was noticed that the drastic reduction in transmitted bandwidth was almost eliminated, thereby proven that multimode fiber can be use in long distance communication provided optical amplifiers are incorporated in between the distance to bust the signal strength.